Adipose‐Derived Mesenchymal Stem Cell Features in Patients with a History of Head and Neck Radiation. Issue 3 (10th June 2016) - San‐Marina, Serban; Voss, Steve; Crespo‐Diaz, Ruben; Wyles, Cody; Behfar, Atta; Stalboeger, Paul; Janus, Jeffrey R.
Abstract : Objectives/Hypothesis: Radiation plays a prominent role in advanced stage head and neck tumors. Often, the radiated area includes adjacent nonmalignant mesenchymal tissue, which contains a mixture of cells that has been shown to accelerate wound healing. The purpose of this study is to determine the long‐term effect of radiation on the expansion potential of adipose‐derived stromal/stem cell (ADSC) tissue and on the ability of resident stem cells in this fraction to undergo phenotypic differentiation. Study Design/Methods: After institutional review board approval, 12 patients with a history of head and neck radiation and pending surgery were enrolled. Adipose tissue was collected from irradiated tissue (XRT) and nonirradiated tissue (NRT) sites. Mesenchymal stem cells were isolated from these populations, with subsequent assessment of cellular kinetics and differentiation potential between harvest sites. Results: Adipose‐derived stromal/stem cells could not be isolated from XRT in six patients due to lack of in vitro cell proliferation. For the remaining six patients, overall cumulative population‐doubling time was longer for XRT relative to NRT (29.3 vs. 11.5 days; P  = 0.02). However, no significant differences were observed in cell generation time or viability. When XRT and NRT ADSC fractions were grown to standardized concentrations and incubated under conditions that induce phenotypic differentiation of resident stem cells, no significant changes in chondrogenic, adipogenic, or osteogenic differentiation were observed. Conclusion: These preliminary observations suggest that irradiated ADSCs close to the surgical site undergo long‐term changes in proliferative capacity. The potential for phenotypic differentiation is retained, however, in ADSCs that survive the irradiation process. Level of Evidence: 2b.